Novel contributions on luminescent apatite-based colloids intended for medical imaging. (January 2014) - Al-Kattan, Ahmed; Santran, Veronique; Dufour, Pascal; Dexpert-Ghys, Jeannette; Drouet, Christophe
The setup of colloidal hybrid nanosystems based on biomimetic calcium phosphate apatites doped with europium ions has recently raised great interest in the pharmacological community, especially due to their bio-inspired character. This is especially relevant in relation with medical imaging for cancer diagnosis. Questions however remain in relation to a number of applicability aspects, some of which have been examined in this contribution. In a first part of this work, we explored further the luminescence properties of such colloidal nanoparticles. We pointed out, upon excitation of europium, the existence of some non-radiative de-excitation via the vibration of O-H oscillators located at the vicinity of the Eu 3+ luminescent centers. The replacement of Eu 3+ by Tb 3+ ions, less prone to non-radiative de-excitation, was then tested in a preliminary way and can be seen as a promising alternative. In a second part of this work, we inspected the possibility to store these colloids in a dry state while retaining a re-suspension ability preserving the nanometer size of the initial nanoparticles, and we propose a functional protocol involving the addition of glucose prior to freeze-drying. We finally showed for the first time, based on titrations of intracellular Ca 2+ and Eu 3+ ions, that folic acid-functionalized biomimetic apatite nanoparticles were able to target cancer cells that overexpress folate receptors on their membrane, which we point out here in the case of T-47-D breast carcinoma cells, as opposed to ZR-75-1 cells that do not express folate receptors. This contribution thus opens new exciting perspectives in the field of targeted cancer diagnosis, thus confirming the promise of biomimetic apatites-based colloidal formulations.